CLINICAL OUTCOMES AND DYNAMICS OF PLATELET-PLASMA AND VASCULAR HEMOSTASIS IN PATIENTS WITH UNSTABLE ANGINA AND CORONARY ARTERY BYPASS GRAFTING - E. A. Medvedeva; L. G. Gelis; V. V. Shumavets; I. I. Russkikh (Евразийский Кардиологический Журнал)
The aim. To evaluate the clinical outcomes and features of the state of the platelet-plasma and vascular hemostasis in patients (pts) with unstable angina and coronary artery bypass grafting (CABG) on-pump and off-pump for the correction of antithrombotic therapy and reduce the number of postoperative cardiovascular events. Material and methods. The study included 146 pts with unstable angina (UA) with a surgical treatment strategy. CG amounted to 106 pts with CABG and a standard approach to drug maintenance. MG comprised 40 pts with CABG and a personalized approach to antithrombotic therapy. Results. In CABG off-pump in pts with UA, an increased in platelet aggregation and activation of platelet hemostasis occurs on the 2nd day of the postoperative period, in CABG on-pump on the 5-7th day. Activation of plasma hemostasis had laboratory manifestations on the 5-7th day of the postoperative period, and is most pronounced in CABG on-pump, compared with CABG off-pump. After 1 month of control, 38,7% pts with UA and CABG were characterized by the presence of high residual platelet reactivity against the background of standard antiplatelet treatment, of which 23,6% retained activation of plasma hemostasis, which is manifested in excess of the normal level of D-dimers, as well as an increased in peak thrombin concentration and endogenous thrombin potential. Patients with UA and CABG who underwent correction of antithrombotic therapy differed from patients with a standard approach to treatment with a significantly lower number of repeated cardiovascular events over 2 years of follow-up (5% versus 22.6%).